Hydroponic Treatment of Nicotiana benthamiana with Kifunensine Modifies the N-glycans of Recombinant Glycoprotein Antigens to Predominantly Man9 High-Mannose Type upon Transient Overexpression - Roychowdhury, Sugata; Oh, Young J.; Kajiura, Hiroyuki; Hamorsky, Krystal T.; Fujiyama, Kazuhito; Matoba, Nobuyuki (Frontiers in Plant Science, 2018)
Nicotiana benthamiana transient overexpression systems offer unique advantages for rapid and scalable biopharmaceuticals production, including high scalability and eukaryotic post-translational modifications such as N-glycosylation. High-mannose-type glycans (HMGs) of glycoprotein antigens have been implicated in the effectiveness of some subunit vaccines. In particular, Man9GlcNAc2 (Man9) has high binding affinity to mannose-specific C-type lectin receptors such as the mannose receptor and dendritic cell-specific intracellular adhesion molecule 3-grabbing non-integrin (DC-SIGN). Here, we investigated the effect of kifunensine, an α-mannosidase I inhibitor, supplemented in a hydroponic culture of N. benthamiana for the production of Man9-rich HMG glycoproteins, using N-glycosylated cholera toxin B subunit (gCTB) and human immunodeficiency virus gp120 that are tagged with a H/KDEL endoplasmic reticulum retention signal as model vaccine antigens. Biochemical analysis using anti-fucose and anti-xylose antibodies as well as Endo H and PNGase F digestion showed that kifunensine treatment effectively reduced plant-specific glycoforms while increasing HMGs in the N-glycan compositions of gCTB. Detailed glycan profiling revealed that plant-produced gp120 had a glycan profile bearing mostly HMGs regardless of kifunensine treatment. However, the gp120 produced under kifunensine-treatment conditions showed Man9 being the most prominent glycoform (64.5%), while the protein produced without kifunensine had a substantially lower Man9 composition (20.3%). Our results open up possibilities for efficient production of highly mannosylated recombinant vaccine antigens in plants.